Generalized Surrogacy and the COVID Crisis - Hansen, Danielle Tumminio (International journal of practical theology, 2022)
This article examines how the systemic sin of neoliberalism affects pandemic relationships, specifically considering how its emphasis on autonomy can result in relational abuse and erode a recognition of our fundamental interdependence as human beings. To contextualize the argument, this article employs a case study of tip baiting in the United States during the COVID-19 crisis to explain how neoliberalism concretely results in harm that can be identified as a form of systemic sin.